The structure of Shigella virus Sf14 reveals the presence of two decoration proteins and two long tail fibers - Sundharraman Subramanian; Hailey R. Kerns; Samantha G. Braverman; Sarah M. Doore (Communications Biology)
Abstract Bacteriophage Sf14 infects the human pathogen Shigella flexneri. A previous low-resolution structure suggested the presence of a decoration protein on its T = 9 icosahedral capsid. Here, we determined high-resolution structures of the Sf14 capsid and neck, along with a moderate-resolution structure of the whole Sf14 tail and baseplate. These structures indicate the capsid has not one, but two different types of decoration proteins: a trimeric β-tulip lattice that covers the entire capsid and a set of Hoc-like proteins that bind preferentially to hexamers at the quasi-3-fold axes of symmetry. The neck also contains two sets of whiskers oriented in opposite directions, and the tail has two types of long tail fibers which may bind different receptors. Based on homology and phylogenetic analysis, Sf14 may be the product of multiple horizontal gene transfer events. The structures presented here can be used to investigate further hypotheses of phage structure-function relationships and structural diversity.